Association between Vaginal Infections and the Types and Viral Loads of Human Papillomavirus: A Clinical Study Based on 4,449 Cases of Gynecologic Outpatients - Wei Wang; Xian-hui Zhang; Mei Li; Chong-hua Hao; Hong-ping Liang (Canadian Journal of Infectious Diseases and Medical Microbiology)
Objective. We here evaluated the association between human papillomavirus (HPV) infection and vaginal infections, including bacterial vaginosis (BV), trichomonas vaginalis (TV), and vulvovaginal candidiasis (VVC). Methods. A total of 4,449 women were enrolled in this study and given gynecological examinations. HPV genotyping and viral load determination were performed using a real-time PCR. Vaginal infections were diagnosed using wet mounts of vaginal secretions, gram-stained vaginal secretion smears, and chemical enzyme kits. Results. In this study, the overall HPV-positive rate was 25.06%, and vaginal infection tended to occur in women with HPV infection (P<0.05). HPV infection tended to occur in BV- and TV-positive women (P<0.05) and not in women with microecological disorders, intermediate type BV, VVC, or coinfection (P>0.05). The most common genotypes were HPV58 and HPV53 in women with normal vaginal microecology and HPV16 and HPV52 in the women suffering from vaginal infection. The viral loads among groups for HPV16 and HPV52 showed no statistically significant differences (P=0.940; P=0.167). Conclusions. Our study revealed that BV and TV are associated with HPV infection, especially high-risk HPV infection, while VVC has no association with HPV infection. Further studies are needed to explore the detailed mechanism.